Late Cretaceous–earliest Paleogene deformation in the Longmen Shan fold‐and‐thrust belt, eastern Tibetan Plateau margin: Pre‐Cenozoic thickened crust?. Issue 10 (6th October 2016) - Tian, Yuntao; Kohn, Barry P.; Phillips, David; Hu, Shengbiao; Gleadow, Andrew J. W.; Carter, Andrew
Abstract: This study presents structural and 40 Ar/ 39 Ar geochronological data from the southern part of the Longmen Shan fold‐and‐thrust belt that forms the eastern margin of the Tibetan Plateau. Investigations focused on hinterland ductile top‐to‐the‐WNW shear deformation, which has been linked previously to late Cenozoic lower crustal flow. Consistent with previous studies, the sense of deformation is mapped as top‐to‐the‐WNW in the Longmen Shan hinterland. The timing of the deformation is constrained by 40 Ar/ 39 Ar geochronological data of recrystallized minerals aligned along the shear foliation as Late Cretaceous–earliest Paleogene, thus predating the inferred late Cenozoic crustal flow. This deformation is contemporaneous with SE verging thrusting and loading along the Longmen Shan front, which formed a coeval ~2–3 km thick foredeep sequence along the southwestern margin of the Sichuan Basin. In the context of the regional geology, this tectonic configuration could result from either extrusion of a crustal wedge or back thrust in a duplex. Compared to other orogens, where similar crustal configurations have been reported, it is speculated that the eastern Tibetan Plateau margin acquired thickened crust and highly elevated topography in Late Cretaceous–earliest Paleogene time. Key Points: Late Cretaceous‐earliest Paleogene hinterland deformation Contemporaneous shortening in the foreland side Pre‐Cenozoic thickened crust in the eastern Tibetan Plateau margin